VARIASI NUKLEOTIDA LOKUS 126 pb DAERAH D-LOOP DNA MITOKONDRIA (mtDNA) PADA INDIVIDU SEGARIS KETURUNAN IBU - Yudianto, Ahmad; Maskjur, Indah Nuraini (Indonesian Journal of Legal and Forensic Sciences (IJLFS), 2012)
The characteristics of mitochondrial DNA (mtDNA) can be used to confirm individual and ethnic identity Madurese group of population represents an ethnic group that until presently preserves their ancestral customs in a harmonious co-existence in with their religion and endogamy remains occurring among them. The purpose of the present study was to determine the presence of the nucleotide variants of 126-bp mtDNA D-Loop region in maternally inherited individuals in several generations of Madurese ethnic group that could later be used as the basis for determining the genetic patterns of the Madurese’s mtDNA in a larger scale. For this purpose, the study carried out nucleotide sequence determination of mtDNA D-Loop region on several Madurese individual by using a sample of epithelial cells of oral cavity. A series of activities including isolation of the samples’ mitochondrial DNA, PCR amplification of mtDNA D-loop region, and sequencing and analysis of the nucleotide sequence of sequencing results was performed in order to determine the nucleotide sequence. The study successfully performed PCR amplification of the 126-bp fragment of mtDNA D-Loop region and determined a 125-bp nucleotide sequence of one Madurese individual. In addition, the study found variants or morphs differing from the Cambridge or Anderson sequences. Ten haplotipe were found in different positions; they were 109A-T, 110G-T. 130C-A, 101G-A, 107G-A, 118T-A, 131T-A, 160T-C, and 161T-A. In addition, a C nucleotide substitution was found at position 129.
Keywords: Mitochondrial DNA; variants; D-Loop; maternally inherited